In the Shadow of Death Archibald Campbell Tait, Archbishop of Canterbury. - Witheridge, John (James Clarke Company, Limited, 2021)
In this, the first biography of Archibald Campbell Tait since his son-in-law, Randall Davidsons in 1891, John Witheridge tells the story of how a Scottish outsider became Queen Victorias favourite Archbishop of Canterbury, and the most powerful since Laud in the seventeenth century.